Beyond the glands; A toll for the forgotten thirst - T R Sowmya; K Ravi (Wolters Kluwer Medknow Publications, 2019)
Sjogren's syndrome, an autoimmune disease of exocrine glands presents in different ways. The disease can present as a single when it is called primary Sjogren's syndrome or may be associated with other autoimmune disorders when it is termed as secondary Sjogren's syndrome the most common association being rheumatoid arthritis. Primary Sjogren's syndrome is a rarity in India. Here we present two rare cases of primary Sjogren's syndrome. The first case in which patient presented with recurrent hypo kalemic paralysis had an isolated renal involvement, in the form of renal tubular acidosis as primary presentation. The second case where patient presented with predominant ataxia was a primary neurological involvement in the form of sensory ganglionopathy.